Avaliação dos efeitos da suplementação com suco de acerola no desempenho e marcadores hematológicos em homens praticantes de crossfit® - Sousa, Francisco Dânio Bastos de Araújo (2024)
Acerola (Malpighia emarginata) is a tropical fruit, with well-developed ultivation in Brazil and which has been gaining global prominence in the economic, harmaceutical industrial and scientific community, as it contains phenolic compounds, flavonoids, isoflavones and a high concentration of Ascorbic acid. Acerola has been used in several studies for its pharmacological properties, especially its antioxidant and anti-inflammatory activities, through in vitro and in vivo approaches. Biocompounds such as flavonoids and anthocyanins, present in acerola, have immunomodulatory effects and suppressive effects on catecholamines, chemokines and reactive oxygen species (ROS) and nitrogen (RNS). CrossFit® is a functional training program, organized into daily sessions using gymnastic movements, weight lifting and monostructural exercises as a basis, practiced at high intensity. This physical training methodology generates enormous metabolic stress, making practitioners susceptible to changes in immunological parameters, endocrine activities and redox status in a single session. Therefore, this study evaluated that upplementation with acerola juice may have improved performance, increasing the number of repetitions between sessions in men practicing CrossFit®, but did not obtain a significant result in hematological parameters.